Arthropod Communities on Young Vegetated Roofs Are More Similar to Each Other Than to Communities at Ground Level - Kyrö, Kukka; Kankaanpää, Tuomas; Vesterinen, Eero J.; Lehvävirta, Susanna; Kotze, David Johannes (Frontiers in Ecology and Evolution, 2022)
Vegetated roofs are human-manufactured ecosystems and potentially promising conservation tools for various taxa and habitats. Focussing on arthropods, we conducted a three year study on newly constructed vegetated roofs with shallow substrates (up to 10 cm) and vegetation established with pre-grown mats, plug plants and seeds to describe pioneer arthropod communities on roofs and to compare them with ground level communities. We vacuum sampled arthropods from the roofs and nearby ground level sites with low, open vegetation, i.e., potential source habitats. We showed that the roofs and ground sites resembled each other for ordinal species richness but differed in community composition: with time the roofs started to resemble each other rather than their closest ground level habitats. Species richness increased with time on roofs and at ground level, but the roofs had consistently less species than the ground sites and only a few species were unique to the roofs. Also, the proportion of predators increased on roofs, while not at ground level. We conclude that vegetated roofs established with similar substrates and vegetation, filter arthropods in a way that produces novel communities that are different from those at ground level but similar to one another. The role of these insular communities in species networks and ecosystem function remains to be investigated.